AKTIVITAS BAKTERI RIZOSFER Actinomycetes DALAM MENDEGRADASI LIMBAH CAIR KELAPA SAWIT - Titis Maria Yusuf; Suwondo Suwondo; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstrack: This research aims to determine the activity of rhizosphere bacterialActinomycetes degrade palm oil liquid waste. The method used in this research isexperimental, using a completely randomized design with 4 treatments and 3 timesreplicates. The degradation treatment of palm oil liquid waste as follows: (1) palm oilliquid waste sterile without bacteria (control), (2) palm oil liquid waste sterile +bacteria Actinomycetes type I, (3) palm oil liquid waste sterile + bacteriaActinomycetes type II, and (4) palm oil liquid waste sterile + bacteria Actinomycetestype III. Rhizosphere bacterial Actinomycetes type II proved the most potential todegrade palm oil liquid waste compared with rhizosphere bacterial Actinomycetestypes I and III. Rhizosphere bacterial Actinomycetes type II can reduce the BOD23.67 mg/L, COD 748.33 mg/L, TSS 21.67 mg/L, pH 7.3, and the total number ofbacteria 80x1010 CFU/mL during incubation day 14. The longer incubation time thecontent of BOD, COD, TSS decreased and pH values towards neutral.Key Words: rhizosphere bacterial Actinomycetes, palm oil liquid waste degradation